AIDS, Poverty, and Hunger: An Overview - Gillespie, Stuart (International Food Policy Research Institute, 2006)
The AIDS epidemic is a global crisis with impacts that will be felt for decades to come. More than 28 million people have died since the first case was reported in 1981. In 2005, AIDS killed 2.8 million people, and an estimated 4.1 million became infected, bringing to 38.6 million the number of people living with the virus around the world; 24.5 million of these people live in Sub-Saharan Africa (where in some countries one in three adults are infected) and 8.3 million live in Asia (UNAIDS 2006).